Inclusion of library staff in the budgeting and collection development processes in Private Universities in Osun and Oyo States, Nigeria - Bakrin, Sirajudeen Femi; Liasu, Jelili Adeyinka (Communicate: Journal of Library and Information Science, 2025)
This paper investigates inclusiveness in budget preparation and collection development in the fifteen NUC-registered private university libraries in the Oyo and Osun States of Nigeria. The study adopted a survey research design targeting the academic librarians and library officers of all fifteen private universities in the two states. Due to the small study population, the total enumeration sampling technique was adopted to select all 111 respondents (academic librarians and library officers). A structured questionnaire was subsequently administered to the respondents to gather data. Eventually, only ninety-seven (97) respondents attended to the questions and the collected data was analysed using descriptive statistics. Findings revealed that though the Collection Development Unit exists in the libraries, the university librarians have appropriated their functions while assigning their lackeys as heads of the unit most times. Also, the study showed high inclusivity in the budgeting process, with all units making necessary contributions. The study concludes by recommending a sustained inclusive and collective budget preparation process, respect for autonomy and job specification of the collection development unit. At the same time, the university libraries should grasp the opportunity of accreditation visits to give their collection a deserved facelift.